Epidemiología de los tumores malignos diagnosticados por histología en el Hospital Manuel Ygnacio Monteros Valdivieso, IESS Loja - Cueva Tapia, Fiama de Lourdes (2019)
Cancer is characterized by an uncontrolled growth of abnormal cells, the entire population is at risk of suffering from either genetic defects or exposure to certain risk factors affecting the lives of almost all, directly or indirectly. The importance of knowing the prevalence of malignant tumors according to gender and age group, the affected organ and the geographic distribution of malignant tumors and relating the main organs affected according to the geographical distribution of the malignancies diagnosed in the Manuel Ygnacio Monteros Hospital Valdivieso, IESS Loja, period June 2014 - June 2016. It was necessary to carry out a non-experimental, cross-sectional, retrospective quantitative study in the Pathology Area of the Manuel Ygnacio Monteros Hospital, with a study sample consisting of 760 cases which met with the inclusion and exclusion criteria disposed. Resulting in the highest prevalence of neoplasms in the female sex in middle age, while in the male sex the older adult is the most affected age group, the majority of cases coming from the canton Loja, nevertheless the distribution of neoplasms is maintained in 14 of the 16 cantons of the province mainly cancer of the colon, stomach, skin, thyroid, cervix and prostate. Key Words: Colon, woman, middle age.